Characterization and comparative study on structural and physicochemical properties of buckwheat starch from 12 varieties. (April 2023) - Gao, Licheng; Van Bockstaele, Filip; Lewille, Benny; Haesaert, Geert; Eeckhout, Mia
Abstract: Buckwheat is an important starch source because of its health benefits. In this study, buckwheat starches isolated from 12 varieties were analyzed based on the morphological, structural and physicochemical properties. The results showed that starch samples from different varieties had high purity with the total starch ranging from 91.29 to 95.11%, while showing significant differences in ash content (0.12–0.25%), protein content (0.26–0.34%) and amylose content (29.55–36.13%), respectively. All samples presented spherical and irregular shapes and typical A-type crystalline structure, but obvious differences in granule size distribution and relative crystallinity (26.37–35.21%) were observed among 12 varieties. Starch samples differed in lamellar structures, showing higher values of thickness of the samples with higher amylose content. In addition, buckwheat starches with higher amylose content showed higher values in light transmittance and rheological properties, while starch samples with lower amylose content obtained higher values in terms of water solubility, swelling power, pasting behaviors and thermal parameters. The principal component analysis and cluster analysis based on starch property parameters indicated that there were significant similarities and differences among 12 varieties, which might be related to the genotypes. This study would provide valuable information for the full use of buckwheat starch in food and non-food industries. Graphical abstract: Image 1 Highlights: Buckwheat starches of 12 varieties collected from 6 countries were studied. The amylose content of buckwheat starch ranged from 29.55 to 36.13%. All samples had spherical and irregular shapes and typical A-type crystallinity. Buckwheat starch with higher amylose content showed lower lamellar parameters. Starch samples differed in water solubility, pasting and rheological properties.